2008
DOI: 10.1111/j.1469-8749.2008.02025.x
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the clinimetric properties of neuromotor assessments for preterm infants during the first year of life

Abstract: This systematic review evaluates assessments used to discriminate, predict, or evaluate the motor development of preterm infants during the first year of life. Eighteen assessments were identified; nine met the inclusion criteria. The Alberta Infant Motor Scale (AIMS), Bayley Scale of Infant and Toddler Development ‐ Version III, Peabody Developmental Motor Scales ‐ Version 2, Test of Infant Motor Performance (TIMP), and Toddler and Infant Motor Examination have good discriminative validity when examined in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
296
0
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(316 citation statements)
references
References 66 publications
(46 reference statements)
3
296
0
17
Order By: Relevance
“…The TIMP has been described as one of the best tools to discriminate between age-appropriate and delayed motor performance in preterm and term infants, and to predict later motor development. 18,19 It was developed to assess functional motor performance in infants between 34 weeks' PMA and 17 weeks' postterm CA. The test can also be used to evaluate the effect of interventions, but the minimum clinically important difference for the TIMP has not yet been identified.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TIMP has been described as one of the best tools to discriminate between age-appropriate and delayed motor performance in preterm and term infants, and to predict later motor development. 18,19 It was developed to assess functional motor performance in infants between 34 weeks' PMA and 17 weeks' postterm CA. The test can also be used to evaluate the effect of interventions, but the minimum clinically important difference for the TIMP has not yet been identified.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…We used assessment tools rigorously evaluated and found to be valid and reliable, 20,24,33 which systematic reviews have shown to be the most accepted. 18,19 Weaknesses of the study were lack of blinding of the staff in the NICU and for some of the assessments at 37 weeks' PMA. These potential biases were minimized because the staff dealing with the infants was not directly involved in the intervention, and the therapist who scored the assessments from the video recordings was unaware of the group assignment.…”
Section: Figurementioning
confidence: 99%
“…It is divided into five subtests: Cognition, Language (receptive and expressive), Motor (gross and fine), Social, and Emotional and Adaptive (10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…These latter, spontaneous arm movements are self‐generated by the infant, they are endogenous, they come from within. And they can be useful in specialized clinical assessments of neuropsychological integrity as well as to become a reference point to assist maternal bonding through recognition of an infant's agency (Brazelton & Nugent, 1995; Einspieler & Prechtl, 2005; Spittle, Doyle, & Boyd, 2008). But these self‐generated “general movements” of infants are not well studied in psychology.…”
Section: Introductionmentioning
confidence: 99%